2020
DOI: 10.26434/chemrxiv.12791954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-Based Drug Design of an Inhibitor of the SARS-CoV-2 (COVID-19) Main Protease Using Free Software: A Tutorial for Students and Scientists

Abstract: This paper describes the structure-based design of a preliminary drug candidate against COVID-19 using free software and publicly available X-ray crystallographic structures. The goal of this tutorial is to disseminate skills in structure-based drug design and to allow others to unleash their own creativity to design new drugs to fight the current pandemic. The tutorial begins with the X-ray crystallographic structure of the main protease (M<sup>pro</sup>) of the SARS coronavirus (SARS-CoV) bound t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…This binding affinity is reasonably well as compared to recently known antiviral drugs. For instance, the binding affinity of the ligand (H 2 L) and copper (II) complex [Cu(L)(phen)]( 1 ) was found to be better than recently docked results of chloroquine (-6.293 kcal/mol), hydroxychloroquine (-5.573 kcal/mol) and remdesivir (-6.352 kcal/mol) with M pro protein [65] . The inhibitory activity results is comparable with our previous work on copper(II) coordination complex [38] .…”
Section: Resultsmentioning
confidence: 70%
“…This binding affinity is reasonably well as compared to recently known antiviral drugs. For instance, the binding affinity of the ligand (H 2 L) and copper (II) complex [Cu(L)(phen)]( 1 ) was found to be better than recently docked results of chloroquine (-6.293 kcal/mol), hydroxychloroquine (-5.573 kcal/mol) and remdesivir (-6.352 kcal/mol) with M pro protein [65] . The inhibitory activity results is comparable with our previous work on copper(II) coordination complex [38] .…”
Section: Resultsmentioning
confidence: 70%
“…Next, the thioester is hydrolyzed by nucleophilic attack of a deprotonated water molecule, the corresponding C-terminal substrate fragment is released, and free enzyme is regenerated. 41 , 42 The flowchart is shown in Figure 1E . In addition to the Cys145-His41 catalytic dyad, a water molecule (H2O cat ) is also involved in the catalytic process by maintaining the protonation state of His41.…”
Section: Crystal Structure and Biological Functions Of Sars-cov-2 3clpromentioning
confidence: 99%
“…Based on the mechanism of coronavirus 3CLpro, the cleavage process of P4-P3-P2-P1-↓-P1’ implies that simulating the chemical structure characteristics of C-terminal segments of substrate peptides holds promise. 42 However, it is very difficult to develop molecular drug scaffolds based on the SARS-CoV-2 structure in the short term. In addition to 96.08% sequence similarity, direct protein skeleton registration analysis, also called the root mean square deviation (RMSD method), showed that SARS-CoV-2 3CLpro and SARS-CoV 3CLpro structures were also highly similar, with an RMSD difference of only 0.884 Å.…”
Section: Using Sars-cov Peptide-like Inhibitors As Highly Effective S...mentioning
confidence: 99%
“…Fortunately, many high‐resolution crystal structures of the M pro in apo and holo states have been resolved and also, several experimental ligand‐binding affinity data have been reported for some different sets of promising inhibitors 1–4,11,22,26,29–33 . The valuable information has provided a golden opportunity for scientists and researchers to understand the molecular mechanisms of ligand‐protein interactions and currently, are being widely used for structure‐based drug discovery, drug repurposing, and high‐throughput screening studies 1,3,4,9,13,14,16,17,21,22,26,27,34–39 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]11,22,26,[29][30][31][32][33] The valuable information has provided a golden opportunity for scientists and researchers to understand the molecular mechanisms of ligandprotein interactions and currently, are being widely used for structure-based drug discovery, drug repurposing, and highthroughput screening studies. 1,3,4,9,13,14,16,17,21,22,26,27,[34][35][36][37][38][39] In this study, we report a comprehensive comparative structural analysis of the M pro substrate binding site for both the unbound (apo) and ligand-bound (holo) states to identify key residues and conserved water molecules in the ligand-binding process. Moreover, we design a new docking protocol in the framework of the ensemble docking strategy.…”
mentioning
confidence: 99%